1999
DOI: 10.1016/s0014-5793(99)00708-5
|View full text |Cite
|
Sign up to set email alerts
|

Cloning of a novel kinase (SIK) of the SNF1/AMPK family from high salt diet‐treated rat adrenal1

Abstract: PCR-coupled cDNA subtraction hybridization was adapted to identify the genes expressed in the adrenocortical tissues from high salt diet-treated rat. A novel cDNA clone, termed salt-inducible kinase (SIK), encoding a polypeptide (776 amino acids) with significant similarity to protein serine/ threonine kinases in the SNF1/AMPK family was isolated. An in vitro kinase assay demonstrated that SIK protein had autophosphorylation activity. Northern blot revealed that SIK mRNA levels were markedly augmented by ACTH … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
120
0

Year Published

2000
2000
2022
2022

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 144 publications
(128 citation statements)
references
References 29 publications
(29 reference statements)
3
120
0
Order By: Relevance
“…2 was first cloned from adrenal glands of rats fed with a high salt diet (1), and its transcription was strongly induced by membrane depolarization in the brain (2). Recent studies unexpectedly demonstrated that SIK1 also plays important functions in liver glucose homeostasis (3) and survival of myocytes (4).…”
Section: Salt-inducible Kinase (Sik)mentioning
confidence: 99%
“…2 was first cloned from adrenal glands of rats fed with a high salt diet (1), and its transcription was strongly induced by membrane depolarization in the brain (2). Recent studies unexpectedly demonstrated that SIK1 also plays important functions in liver glucose homeostasis (3) and survival of myocytes (4).…”
Section: Salt-inducible Kinase (Sik)mentioning
confidence: 99%
“…Because our anti-SIK1 antibody cross-reacted with SIK2 protein, we could not determine the content and activity of SIK1 protein in these tissues. However, a possibility remains that SIK1, which was originally described as "salt-inducible kinase" (26), might be the kinase responsible for phosphorylation of Ser 789 in IRS-1 in the livers of diabetic animals. Taken together, we propose here that in the diabetic animals, SIK2 in white adipose tissues and SIK1 in brown adipose tissues, livers, and skeletal muscles might be involved in the disturbance of the insulin signaling occurring in these tissues and therefore might play important pathogenic roles in the development of type 2 diabetes.…”
Section: Sik2 Is Activated In White Adipose Tissues Of Diabetic Mice-mentioning
confidence: 99%
“…The serine phosphorylation of IRS proteins would modulate the efficiency of the insulinsignaling cascade (8, 9) and eventually render the animals resistant to insulin stimulation (10, 11). Molecular identification of several protein kinases responsible for the serine phosphorylation of IRS proteins has been reported (12-24).Salt-inducible kinase (SIK) was first cloned from the adrenal glands of rats fed a high salt diet (25,26). It is a serine/ threonine protein kinase that belongs to a sucrose-nonfermenting-1 protein kinase/AMP-activated protein kinase (AMPK) family.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Salt-inducible kinase (SIK) was identified as a serine/threonine protein kinase induced in the adrenal glands of high-salt diet-fed rats (33,34). When Y1 mouse adrenocortical tumor cells were incubated with ACTH, the cellular levels of mRNA, protein, and kinase activity of SIK were elevated within 1 h through the cAMP/PKA signaling mechanism, and then after a few hours the levels declined (35).…”
mentioning
confidence: 99%